2020
DOI: 10.4103/ams.ams_19_20
|View full text |Cite
|
Sign up to set email alerts
|

Mandibular retromolar foramen and canal - A systematic review and meta-analysis

Abstract: Introduction: The retromolar fossa is a small triangular area posterolateral to 3rd molar region in the mandible. The retromolar fossa often contains the retromolar foramen (RMF) as an anatomical variant. When the RMF is present, the foramen is connected with the mandibular canal (MC) through another canal known as the retromolar canal (RMC). RMC contains neurovascular bundle, which gives additional supply to the mandible. Although few studies have been conducted in past, a lacunae in comprehensiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 12 publications
0
11
0
Order By: Relevance
“…RMC was classified into three types based on the CT findings (Figure 6) 3 : type A, vertical course; type B, curved course; and type C, horizontal course. The most common type of RMF is type A, which runs in the posterosuperior direction.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…RMC was classified into three types based on the CT findings (Figure 6) 3 : type A, vertical course; type B, curved course; and type C, horizontal course. The most common type of RMF is type A, which runs in the posterosuperior direction.…”
Section: Discussionmentioning
confidence: 99%
“…3 The branches of the inferior alveolar nerves (IAN) passing through the RMC provide additional supply to the surrounding mucosa and temporal and buccal muscles, and the branches of the inferior alveolar arteries anastomose with the branches of the buccal and facial arteries. 3 Although the presence of RMC and RMF is neglected in textbooks, it occasionally causes severe hemorrhage and nerve damage during surgery. [2][3][4][5] Herein, we report a case of pulsatile hemorrhage during extraction of a mandibular third molar and removal of a surrounding cyst-like lesion.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the review of Shah and Mehta [24], retromolar canal comprised 3.2% to 93.5% of dry mandibles. Tis range was fve times wider than ours.…”
Section: Agreement and Disagreement With The Previous Reviewsmentioning
confidence: 99%
“…One literature review stated that BMC ranged between 0.05% and 69% of the population [12]. In the review of Shah and Mehta [24], retromolar canal, one type of BMCs, revealed 3.2% to 93.5% of dry mandibles. Castro and fellows [25] contributed classifcations of BMCs.…”
Section: Introductionmentioning
confidence: 99%